2007
DOI: 10.1002/col.20329
|View full text |Cite
|
Sign up to set email alerts
|

Sensor‐response‐ratio constancy under changes in natural and artificial illuminants

Abstract: We have analyzed the constancy of the response ratio for cones, second-stage mechanisms, and CCD sensors when daylight or an artificial illuminant (A, F2, F7, and F11) is changed to an equal-energy illuminant (E) in scenes containing natural and artificial objects. The response ratios were always found to be roughly constant for all the sensors. For daylight, we have deduced mathematical expressions, which relate the values of these ratios with the correlated color temperature (CCT) and applied these expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
(36 reference statements)
3
6
0
Order By: Relevance
“…This linear relationship indicates that the ratio of the excitations under illuminant changes for each cone class remains roughly constant for all objects. The same ratio constancy stands for artificial sensors, as we have proved in a previous work [29].…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…This linear relationship indicates that the ratio of the excitations under illuminant changes for each cone class remains roughly constant for all objects. The same ratio constancy stands for artificial sensors, as we have proved in a previous work [29].…”
Section: Introductionsupporting
confidence: 61%
“…These relationships occur for a variety of soft daylight spectral power distributions (SPDs) and for artificial illuminants. Romero et al [29] have proved that these relationships are also preserved between the response of artificial receptors (like the ones present in RGB camera channels) under different illuminants. Depicting in the y axis the response of one camera sensor (R, G, or B digital counts of the captured image) for the illuminant present in the scene, and in the x axis the response of the same sensor under a theoretical illuminant, such as an E illuminat (i.e., an equienergetic illuminant), linear relationships appear, with a high correlation coefficient, as we have previously mentioned.…”
Section: A Constant Ratios At Different Distancesmentioning
confidence: 96%
See 1 more Smart Citation
“…When, for any specific cone receptor [33], the excitation values of several objects under a specific illuminant are represented as a function of those obtained under another illuminant, the result is a straight line with a high correlation coefficient [1]. Some color constancy theories used to develop object-recognition algorithms are also based on cone-excitation ratio constancy [9,11]. Figure 7(a) shows an example of cone-excitation ratio constancy.…”
Section: Cone-excitation Ratios and Distancementioning
confidence: 99%
“…The appearance of objects does not change for different days, hours of the day, or atmospheric conditions in spite of the colorimetric changes provoked by the changes in illumination. Working with a wide range of objects, several authors [1,[11][12][13][14] have found a linear relationship with a high correlation coefficient representing the pairs of excitation values for each cone photoreceptor (L, M, or S) determined for each object under daylight illumination at two different color temperatures. Foster and Nascimento [12] explain the color-constancy phenomenon based on these linear relationships.…”
Section: Introductionmentioning
confidence: 99%